Features of multimorbidity in elderly and senile people with hypertension - V. V. Popov; I. A. Novikova; M. V. Trokhova (Российский кардиологический журнал)
Aim. To reveal the features of multimorbidity in elderly and senile people with hypertension (HTN).Material and methods. A total of 70 elderly and senile hypertensive patients were examined at one of the Arkhangelsk outpatient clinics (from 60 to 90 years old; mean age — 69,14±1,34 years), including those aged 60-74 years (n=56; (80,0%) and 75 years and older (n=14; 20,0%). We assessed the questionnaire survey data, the outpatient medical records, the clinical status, and the cumulative illness rating scale for geriatrics (CIRS-G).Results. The analysis showed a high prevalence of multimorbidity in elderly and senile people with HTN, which was found in all patients. On average, an elderly patient with HTN has 6 diseases that are pathogenetically interrelated and unrelated, while a senile patient has 8 diseases. The most common comorbidities were gastrointestinal (81,43%), musculoskeletal (77,14%) and endocrine (77,14%) diseases. Among the cardiovascular comorbidities in the elderly with HTN, the following were more common: heart failure (54,29%), coronary artery disease (angina pectoris — 41,43%) and cerebrovascular diseases (28,57%) (stroke/transient ischemic attack, vascular encephalopathy). Patients with HTN took an average of 6 different drugs at the same time. There was moderate comorbidity level in the elderly patients and a high one in those of senile age.Conclusion. In elderly and senile patients with HTN, there is a high prevalence of multimorbidity, which must be taken into account when preventing polypharmacy.